PENGARUH EKSTRAKURIKULER PRAMUKA TERHADAP JIWA KEPEMIMPINAN SISWA SMAN 1 BANGUN PURBA - Lestari, Ikma; Arianto, Jumili; Gimin, Gimin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out whether there is an influence of scouting extracurriculars on students' leadership skills. The method in this research is descriptive quantitative, data analysis was carried out on the research sample using a statistical approach. The data collection instrument uses a questionnaire consisting of 32 questions. The population in this study were all students of SMAN 1 Bangun Purba, totaling 316 students with a sample of 79 respondents. Based on the research results, it was found that there was a positive influence between scout extracurriculars on the leadership spirit of students at SMAN 1 Bangun Purba. This can be proven by simple linear regression analysis using SPSS, namely Ŷ= 40,705 + 0.374 The influence of scout extracurricular activities (independent variable) on leadership skills (dependent variable) is 16.1%. Meanwhile, 83.9% (100-16.1%) was influenced by other variables not examined in this study.